2017
DOI: 10.3390/nu9040391
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein Decreases Cyclooxygenase-2 and Interleukin-17 Expression and Attenuates Inflammatory Damage in Colonic Samples from Ulcerative Colitis Patients

Abstract: Oleuropein (OLE) is the major phenolic secoiridoid of olive tree leaves, and its antioxidant and anti-inflammatory activities have been demonstrated in in vitro and in vivo animal models. The aim of this study was to investigate the activity of OLE in the colonic mucosa from patients with ulcerative colitis (UC). Biopsies obtained during colonoscopy from 14 patients with active UC were immediately placed in an organ culture chamber and challenged with lipopolysaccharide from Escherichia coli (EC-LPS) at 1 μg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 40 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…As discussed previously, our results indicate an important role for MSC in reducing the pathogenic Th17 response in experimental colitis, in agreement with Godoi et al [16], who observed reduced levels of IL-17 after bone marrow transplantation for the treatment of experimental intestinal inflammation. Th17 cells and the cytokine IL-17 have been found at elevated levels in intestinal tissue and serum from patients with IBD, confirming the finding that this pattern of immune response contributes to the development of the disease [64]. Interestingly, we also show that MSC infusion reduced the frequency of IL-17/IFN-γ double-producing cells at spleen, which was followed by a decreased accumulation of neutrophils in the colon of treated mice.…”
Section: Discussionsupporting
confidence: 88%
“…As discussed previously, our results indicate an important role for MSC in reducing the pathogenic Th17 response in experimental colitis, in agreement with Godoi et al [16], who observed reduced levels of IL-17 after bone marrow transplantation for the treatment of experimental intestinal inflammation. Th17 cells and the cytokine IL-17 have been found at elevated levels in intestinal tissue and serum from patients with IBD, confirming the finding that this pattern of immune response contributes to the development of the disease [64]. Interestingly, we also show that MSC infusion reduced the frequency of IL-17/IFN-γ double-producing cells at spleen, which was followed by a decreased accumulation of neutrophils in the colon of treated mice.…”
Section: Discussionsupporting
confidence: 88%
“…OLE inhibited canonical and noncanonical inflammasome signaling pathways [50] J774 LPS-stimulated macrophages 50 µM OLE inhibited LPS-induced NO production without affecting cell viability [117] OL reduced the expression of COX-2 and IL-17 in samples treated with OL. In addition, OL ameliorated inflammatory tissular damage [207]…”
Section: Diet Supplemented With 1% Olmentioning
confidence: 94%
“…Recently, a study by Larussa T. et al [68] demonstrated that the administration of OleA on colonic biopsies taken from ulcerative colitis patients led to a decrease of COX-2 and IL-17 levels, considerably reducing the inflammation of the colonic tissue. This evidence encourages the use of oleuropein as an inflammation-modulator.…”
Section: Oleuropein As An Anti-inflammatory and Cvd Protective Agentmentioning
confidence: 99%